Определение величины утяжины в процессе радиально-продольного выдавливания в разъемных матрицах - Алиева, Л. И.; Абхари, П. Б.; Гончарук, К. В. (НТУ "ХПИ", 2014)
Рассмотрен процесс комбинированного радиально-продольного выдавливания полых деталей в разъемных матрицах и проведено моделирование методом конечных элементов с использованием программного продукта QForm 2D. Выявлены характерные для процесса отклонения формы детали в виде утяжины, расположенной на внутренней поверхности детали в зоне формирования фланца, и установлена зона параметров, при которых возможно получение деталей без дефектов.

The simulation of combined radial extrusion process for hollow member having an axial appendage and the flange with multiple ram by the finite element method with the software engineering program is named QForm 2D considered. The deformation state research in the combined radial extrusion with work pieces such as aluminum alloys and lead technical was performed. The characteristic deformation in workpiece with defect as dimple on the inner surface in the zone of deformation with the flange for the process was determined. In the combined radial extrusion process with multiple ram researched the stress strain analysis and change of deformation in different steps with different technical parameters. Results of deformation components for different steps were shown. It is defined that in certain ratio of geometric parameters will be appeared defect is named dimple. For determining dimple in this process was drawn a diagram on geometric parameters.
Determination of dimple in the radial extrusion process with multiple ram
Keywords: радиально-продольное выдавливание; разъемные матрицы; утяжина; метод конечных элементов; radial extrusion; multiple ram; dimple; finite element method